Density and species diversity of mangrove flora in Leuweung Sancang Nature Reserve, Garut, West Java, Indonesia - AFRI IRAWAN; TOPIK HIDAYAT; TINA SAFARIA NILAWATI; AZHAR F.N. BANGIEL; DAFFA’ M. IQBAL; SHAYREEN SALSABILA NADJMI; KARINA EKI MARTHA; REZA RAIHANDHANY (Society for Indonesian Biodiversity, 2026)
Abstract. Irawan A, Hidayat T, Nilawati TS, Bangiel AFN, Iqbal DM, Nadjmi SS, Martha KE, Raihandhany R. 2026. Density and species diversity of mangrove flora in Leuweung Sancang Nature Reserve, Garut, West Java, Indonesia. Biodiversitas 27 (5): d270532. https://doi.org/10.13057/biodiv/d270532. Mangroves are an ecosystem of considerable ecological importance, situated in the coastal tidal zone and characterized by an overgrowth of plant species capable of surviving in inundated seawater zones. A comprehensive study of the Leuweung Sancang mangrove site reveals the presence of mangrove flora, though further study is necessary to describe the species diversity of this ecosystem fully. This study aimed to analyze the extent of mangroves, stand density, and floristic composition across seven mangrove blocks (Cibaluk, Cikabodasan, Cikolomberan, Cipalawah, Sakad, Cipunaga, and Cibako). Field surveys were conducted using block-based exploration combined with radius-based sampling, and voucher specimens were deposited in the Herbarium of Biology at Universitas Pendidikan Indonesia. Spatial boundaries were mapped using GPS-based KML conversion to GIS shapefiles. Species diversity was assessed using the Shannon-Wiener index (H′) and Pielou’s evenness (E), as well as the Sørensen-Dice similarity index and Non-metric Multidimensional Scaling ordination (NMDS) for differentiation among blocks. A total of 17 mangrove species across 10 families were recorded, with the Rhizophoraceae as the dominant family. Sonneratia alba showed the highest relative abundance (27%), followed by Rhizophora apiculata (19%) and Aegiceras corniculatum (13%). Total mangrove coverage reached 40.57 ha. Species diversity varied among blocks, with the highest value recorded in Cibako (H′ = 1.87), indicating moderate diversity, while other blocks showed lower values. Evenness values suggested uneven species distribution due to dominance by a few taxa. Similarity analysis and NMDS showed that Cipunaga, Cibako, Cipalawah and Sakad had similar species composition. The findings indicate that the biodiversity of mangrove species in the study area is suitable and supports the reproduction and development of mangrove plants. A comprehensive compilation of diversity data can serve as a crucial element in ecosystem management within conservation areas and support monitoring and future strategies by the Natural Resources Conservation Agency.